Abolition of Capital Punishment and Public Opinion - Sandheep P.N (International Journal of Advanced Science and Technology, 2020)
As per the existing Indian social scenario the punishment is a method of schooling in which lawbreakers are corrected. Our penal system can be alienated in to three as ancient period, medieval period and modern period. At the time of ancient period the punishment is decided on religious ideology.  In the medieval stage we have seen the arrival of different civilized and scientific theories, such as the notion of deterrent, preventive and reformative ideology. These all penal theories have their own merits and demerits. At present, in the welfare state program, we are following the ideology of reformation with prevention. Fortunately in India, there is great argument among social scientists and criminologist regarding the identification of best practice in prison system, especially by the eradication of capital punishment. Hence, we piloted a study to find out the percentage of both supporters and protesters of the capital punishment.  For this quick research investigator selected 100 students from a college in Kerala state regardless the gender differences, to collect the opinion on this regard. And subsequently investigator find only 15 percentage of students, who are supporting the elimination of capital punishment and remaining 85 percentages is not in favor of abolition of capital punishment. By this study we understood the opinion of the society on the policy of abolition of capital punishment.